The emerging role of osteoclasts in the treatment of bone metastases: rationale and recent clinical evidence - Liu, Youjun; Chen, Huanshi; Chen, Tong; Qiu, Guowen; Han, Yu (Frontiers in Oncology, 2024)
The occurrence of bone metastasis is a grave medical concern that substantially impacts the quality of life in patients with cancer. The precise mechanisms underlying bone metastasis remain unclear despite extensive research efforts, and efficacious therapeutic interventions are currently lacking. The ability of osteoclasts to degrade the bone matrix makes them a crucial factor in the development of bone metastasis. Osteoclasts are implicated in several aspects of bone metastasis, encompassing the formation of premetastatic microenvironment, suppression of the immune system, and reactivation of quiescent tumor cells. Contemporary clinical interventions targeting osteoclasts have proven effective in mitigating bone-related symptoms in patients with cancer. This review comprehensively analyzes the mechanistic involvement of osteoclasts in bone metastasis, delineates potential therapeutic targets associated with osteoclasts, and explores clinical evidence regarding interventions targeting osteoclasts.